Pengembangan Kompetensi Berbasis Nilai Tengka - Badriyah, Khoirina; listiana, Heni; Jannah, Faridatul; Hestiarini Utami, Tika (Postmodernism: Indonesian Journal of Multidisciplinary Islamic Studies, 2024)
The development of teacher competence should not only focus on technical and pedagogical aspects but also integrate relevant local cultural values to foster character building and professionalism. This study aims to develop teacher competence based on the tengka values. The research employs a library research method. The findings reveal that integrating tengka values into teacher competence development enhances professional performance, fosters positive relationships between teachers and students, and strengthens a collaborative work culture within the school environment. This development model also encourages teachers to serve as role models in practicing ethical values both inside and outside the classroom. These findings make a significant contribution to designing holistic teacher training strategies that balance professional skills with character enhancement rooted in local cultural values.